2016
DOI: 10.1097/pts.0000000000000125
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-sectional Analysis Investigating Organizational Factors That Influence Near-Miss Error Reporting Among Hospital Pharmacists

Abstract: Inadequate error feedback to staff and insufficient preventative procedures increase the likelihood that near-miss errors will be underreported. Hospitals seeking to improve near-miss error reporting should improve error-reporting infrastructures to enable feedback, which, in turn, would create a more preventative system that improves patient safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…While some studies reported the negative impact of improper feedback, some reported the positive impact of appropriate feedback. Specifically, it was evident that feedback to the reporting person about the error supports the provider who committed the error and communication openness regarding errors all improved reporting of ME [14,22,27,29,31,36,[40][41][42]. [17,21,40,42].…”
Section: Lack Of Feedbackmentioning
confidence: 99%
See 1 more Smart Citation
“…While some studies reported the negative impact of improper feedback, some reported the positive impact of appropriate feedback. Specifically, it was evident that feedback to the reporting person about the error supports the provider who committed the error and communication openness regarding errors all improved reporting of ME [14,22,27,29,31,36,[40][41][42]. [17,21,40,42].…”
Section: Lack Of Feedbackmentioning
confidence: 99%
“…It has been observed that when hospital administrators' responses to ME focus on the individuals, rather than the system, reporting rates of ME decrease [21]. Additionally, the lack of safety culture and error prevention programs is associated with underreporting [27]. On the other hand, work environments with a strong teamwork perception and psychological safety amongst employees are associated with better reporting of ME [30,32].…”
Section: Lack Of Feedbackmentioning
confidence: 99%
“…However, all three groups tended to strongly agree that they were more likely to report near-misses if feedback was given (62 per cent of nurses, 56 per cent of doctors and 57 per cent of technicians). Van Spall et al (2015) and Patterson and Pace (2016) had similar findings within their studies, with the later stating that the absence of a feedback system for reported errors may be a barrier for learning and deters doctors from further reporting errors. In addition, the response of the doctor interviewed regarding the feedback also suggested that the lack of feedback may also be perceived by the doctors as lack of respect from management.…”
Section: Feedbackmentioning
confidence: 56%
“…However, due to its salient nature, it is more di cult to grasp and learn from than that of adverse events; for example, a recent study revealed that there were only 25 near misses reported in a Chinese tertiary hospital in 2018, much less than the number of adverse events(6). Despite the importance of near miss organizational learning, most studies concerned the prevalence, contributing factors, the underreporting issue and the quality improvement project (7,8), only a few tried to study near miss through the organizational learning perspective, and most of them were without the guidance of organizational learning theory (9,10).…”
Section: Introductionmentioning
confidence: 99%